A psychometric evaluation of the Concise Health Risk Tracking Self-Report (CHRT-SR)- a measure of suicidality-in patients with stimulant use disorder. (July 2018) - Sanchez, Katherine; Killian, Michael O.; Mayes, Taryn L.; Greer, Tracy L.; Trombello, Joseph M.; Lindblad, Robert; Grannemann, Bruce D.; Carmody, Thomas J.; Rush, A. John; Walker, Robrina; Trivedi, Madhukar H.
Abstract: Stimulant use disorders are both common and associated with suicidal ideation and attempts. The psychometric properties of the 12-item Concise Health Risk Tracking Scale Self-Report (CHRT-SR), a measure that was created to assess suicidal thinking and several factors associated with a propensity to act, has been established in persons with mood disorders. This is a secondary analysis to assess the CHRT-SR in 302 stimulant abusing patients that had participated in a clinical trial. A confirmatory factor analysis (CFA) was conducted to assess the factor validity of the 12-item CHRT-SR model with a second-order Propensity factor. The CHRT-SR total score and 2 factor scores (Propensity and Suicidal Thoughts) demonstrated acceptable internal consistency and test-retest reliabilities. These two subscales and the total score were modestly but significantly associated with measures of depression and life satisfaction, demonstrating construct validity. Two additional items assessing Impulsivity were also analyzed, and demonstrated acceptable internal consistency, test-retest reliability, and construct validity. The CHRT-SR appears to be a reliable and valid tool to assess suicidality in persons with stimulant use disorder.